2015
DOI: 10.1128/jcm.00545-15
|View full text |Cite
|
Sign up to set email alerts
|

Tracking Nosocomial Klebsiella pneumoniae Infections and Outbreaks by Whole-Genome Analysis: Small-Scale Italian Scenario within a Single Hospital

Abstract: f Multidrug-resistant (MDR) Klebsiella pneumoniae is one of the most important causes of nosocomial infections worldwide. After the spread of strains resistant to beta-lactams at the end of the previous century, the diffusion of isolates resistant to carbapenems and colistin is now reducing treatment options and the containment of infections. Carbapenem-resistant K. pneumoniae strains have spread rapidly among Italian hospitals, with four subclades of pandemic clonal group 258 (CG258). Here we show that a sing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
35
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(41 citation statements)
references
References 42 publications
4
35
0
Order By: Relevance
“…The rapid spread of K pneumoniae all over the world in the hospital settings is mostly because of the common occurrence of MDR strains. 21 The present study showed that K pneumoniae isolates were recovered from 42/250 (16.8%) of HAI cases. Similar findings were reported by other researchers.…”
Section: Discussionsupporting
confidence: 50%
“…The rapid spread of K pneumoniae all over the world in the hospital settings is mostly because of the common occurrence of MDR strains. 21 The present study showed that K pneumoniae isolates were recovered from 42/250 (16.8%) of HAI cases. Similar findings were reported by other researchers.…”
Section: Discussionsupporting
confidence: 50%
“…; Onori et al . ). In a study performed in 2012 in the north‐west of Italy, among all the isolates of K. pneumoniae , 17·5% were KPC‐producing strains, more frequently isolated in tertiary care referral hospitals and from urine samples (50%) (De Rosa et al .…”
Section: Discussionmentioning
confidence: 97%
“…Later on the circulation of ESBL strains at the end of the last century, the spread of isolates resistant also to the 'last line of defence' antibiotics, that is, carbapenems, has drastically reduced treatment options and diffusion containment. Particularly, carbapenem-resistant K. pneumoniae strains belonging to the clonal group 258 (CG258), comprising ST258 and ST512, have rapidly disseminated and are frequently isolated (Chmelnitsky et al 2013;Pulcrano et al 2014;Angeletti et al 2015;Onori et al 2015). In a study performed in 2012 in the northwest of Italy, among all the isolates of K. pneumoniae, 17Á5% were KPC-producing strains, more frequently isolated in tertiary care referral hospitals and from urine Quantitative biofilm production assay 7·5 7·2 6·9 6·6 6·3 6·0 5·7 5·4 5·1 4·8 4·5 4·2 3·9 3·6 3·3 3·0 2·7 2·4 2·1 1·8 1·5 1·2 0·9 0·6 0·3 0·0 0 3 6 9 1 2 1 5 1 8 2 1 2 4 2 7 3 0 3 3 3 6 3 9 4 2 4 5 4 8 5 1 5 4 5 7 6 0 6 3 6 6 6 9 7 2 7 5 7 8 8 1 8 4 8 7 9 0 9 3 9 6 9 9 1 0 2 1 0 5 1 0 8 1 1 1 1 1 4 1 1 7 1 2 0 samples (50%) (De Rosa et al 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Genomic data are usually used to determine overall antibiotic resistance and virulence backgrounds, 96,97 evolution/adaptation under antibiotic selective conditions or diverse environments, 98,99 and clonal relationship of bacteria in different settings or geographic regions. 87,100 For instance, Wright and colleagues, 101 characterizing 49 Acinetobacter baumannii isolates from 1 US integrated hospital system with the Illumina method, observed wide variations in gene content, even among strains that were almost identical phylogenetically. Transfer of mobile genetic elements, mobilization of insertion sequences, and genome-wide homologous recombination contributed to this diversity.…”
Section: Whole-genome Sequencingmentioning
confidence: 97%